(untitled) (Journal of Hama University, 2024)
The research aims to study Feng Shui in order to help create criteria for a balanced future urban built environment. To do so, the study followed the descriptive analytical approach. The traditional built environment in the Old City of Damascus was considered as a case study model. The research dealt with (feng shui) through the theories of formalism and Chi, reaching two criteria. The two criteria that were reached were applied to the traditional built environment. One of the most important results is that the traditional built environment, according to feng shui standards, achieved a result of 75 percent conformity with the site selection criteria and 86.7 percent with the quality of the indoor built environment. In the end, the study presented, through the lessons learned from the case, and by reviewing all the literature related to the subject, formulating a set of useful recommendations for developing standards for a balanced future built environment, the most important of which is the use of feng shui in developing standards for a future built environment and benefiting from the experience accumulated in the traditional built environment in the Old City of Damascus, This is to enhance the relationship between the trilogy of the built environment, the surrounding environment, and the human being.